Buckling of wires in embedded gel wax - Mohamed Ashiq Mohamed Jalal (Nanyang Technological University, 2022)
In this report, we would be reporting on the numerical study of buckling of thin wires which are embedded in gel wax, which might lead to debonding or even failure at times. A common cause of failure, buckling, is present under Axial compression. Characteristics of buckling can be seen by a naked human eye most of the time. The analysis of the buckling of thin wire would be in the application of Wearable electronic devices and even medical robotics. For this study, the gel wax will be acting as the polymeric matrix. Reason being that it is 100% transparent. Thus visibility would not be an issue. It will also be easier when apply pressure at the side to compress the thin wires and see if they buckle. Two main parameters would be when the wires are compressed normally and when they are compressed with 5 Pre-twists in one direction. Apart from the main two parameters, two other parameters are also introduced such as the various depth the wires are embedded in and the different diameters used. Only one material is used in this study, which is nylon copolymer. Properties of the Nylon Copolymer will be collated from the DSC Test. Trends would observe based on the results of all the experiments. How the various parameters has influenced the results would be gathered. Based on this, future research could be carried out with more parameters to improve the results and narrow down the research area. With the rise in electronics for wearable devices and medical robotics, there has been a steep growth of interest in thin wires buckling patterns. This experimental study would provide more insight on buckling based on multiple parameters.